2017
DOI: 10.1016/j.ejpal.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Psychological Abuse Experienced in Groups Scale

Abstract: The aim of this study is the development and analysis of the psychometric properties of a new instrument to assess the possible psychological abuse experienced in a group setting. The Psychological Abuse Experienced in Groups Scale was administered to 138 people who self-identified as former members of abusive groups. An exploratory factor analysis revealed a common factor, which showed appropriate reliability. The scale scores were correlated with a prior measure aimed to assess group abusiveness, providing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…For the aforesaid, it would be advisable to expand the search with variables which, even if not closely associated with SB for future research, at least should provide important information as, for instance, sexual orientation, since different studies show that groups of Lesbians, Gays, Bisexuals, and Transsexuals have a higher risk of SB (Eisenberg & Resnick, 2006;Haas et al, 2010;Harris, 2013;Liu & Mustanski, 2012;Power et al, 2016). In view of all this, intervention and/or prevention plans (with instruments that detect, for example, psychological abuse; see Saldaña, Rodríguez-Carballeira, Almendros, & Escartín, 2017) can be set up and targeted at groups that are more frequently associated with SBs. Other aspect to be mentioned is that in the flow chart a number of duplicate studies can be found in lower amount than studies excluded because they did not meet the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For the aforesaid, it would be advisable to expand the search with variables which, even if not closely associated with SB for future research, at least should provide important information as, for instance, sexual orientation, since different studies show that groups of Lesbians, Gays, Bisexuals, and Transsexuals have a higher risk of SB (Eisenberg & Resnick, 2006;Haas et al, 2010;Harris, 2013;Liu & Mustanski, 2012;Power et al, 2016). In view of all this, intervention and/or prevention plans (with instruments that detect, for example, psychological abuse; see Saldaña, Rodríguez-Carballeira, Almendros, & Escartín, 2017) can be set up and targeted at groups that are more frequently associated with SBs. Other aspect to be mentioned is that in the flow chart a number of duplicate studies can be found in lower amount than studies excluded because they did not meet the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The development of measures of group psychological abuse has been the aim of several studies (Bohm & Alison, ; Chambers, Langone, Dole, & Grice, ; Saldaña, Rodríguez‐Carballeira, Almendros, & Escartín, ; Winocur, Whitney, Sorensen, Vaughn, & Foy, ; Wolfson, ). However, there is still a need for standardized instruments adapted and validated across different cultures (Almendros, Gámez‐Guadix, Carrobles, & Rodríguez‐Carballeira, ), especially to allow cross‐cultural comparisons of individual experiences of group psychological abuse.…”
mentioning
confidence: 99%
“…Despite the strengths of the GPA, the lack of a comprehensive semantic definition of group psychological abuse that clearly differentiates its operative components may have led to certain limitations related to its content (Saldaña et al, ). First, there is an underrepresentation of some abusive strategies that experts consider severe, such as control over information, which was not represented in any item on the scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results contrast with those obtained in the original study, where the EAPA-P was administered to a sample of 101 women victims of gender violence (Porrúa-García et al, 2016), and evidence was found for a two-factor structure that differentiated between direct and indirect PA strategies. Although some studies argue that PA is multidimensional (i.e., Murphy & Hoover, 1999), in other studies that have evaluated the abuse applied in the context of an intimate relationship (i.e., Jones, Davidson, Bogat, Levendosky, & VonEye, 2005) and in abusive groups (i.e., Saldaña, Rodríguez-Carballeira, Almendros, & Escartín, 2017), evidence has been found for the unidimensionality of the construct. In this regard, the PA strategies included in the taxonomy proposed by Rodríguez-Carballeira et al (2014), and represented in the items on the EAPA-P, could be components of the same phenomenon that tend to occur simultaneously in abusive relationships.…”
Section: Discussionmentioning
confidence: 99%